Regulatory Asymmetry and Media Sovereignty in Indonesia: Governing OTT Platforms in the Digital Era - Zulkarnain, Iskandar; Hanim, Farida; Masril, Munzaimah; Purba, Arief Marizky; Pribadi, Muhammad Akbar; Sinaga, Randa Putra Kasea (Journal of Cultural Analysis and Social Change, 2025)
The presence of Over-the-Top (OTT) platforms such as Netflix, Disney Hot Star, Prime, and VIU has disrupted the traditional broadcasting ecosystem in Indonesia. These global platforms have not only changed media consumption patterns, but also caused regulatory asymmetry because they operate outside the national broadcasting legal framework. This study aims to analyze the impact of the regulatory vacuum surrounding OTT on Indonesia's media sovereignty, highlighting the forms of regulatory asymmetry that have emerged. The method used is a qualitative approach with a descriptive-exploratory design, through policy document analysis, semi-structured interviews with regulators, academics, and industry players, as well as an international literature review on digital media regulation. The results of the study show that there are three main forms of inequality: first, legal and fiscal inequality, because OTTs are not subject to the licensing and taxation obligations that apply to national media. Second, content standard inequality, because conventional broadcasting institutions are required to comply with P3SPS regulations while OTTs are relatively free. Third, economic inequality, as OTT's dominance in advertising and subscriptions is not balanced by its contribution to the domestic creative industry. These findings emphasize the urgency of technology-neutral regulatory reform and the principle of digital justice to ensure a level playing field among media players in Indonesia. Theoretically, this study expands the concept of regulatory asymmetry with an institutional fragmentation perspective and offers a digital justice framework as a normative approach in media sovereignty studies.